The Effect of Body Image and Social Comparison towards Life Satisfaction in Adolescents with Acne Vulgaris - Anjainah, Nur 'Azizah Laili Anjainah; Jainudin (Analitika: Jurnal Magister Psikologi UMA, 2024)
Life satisfaction levels are known to be lower in people with acne vulgaris than in those who do not have this dermatological disease. This research looked at whether there was an effect between body image and social comparison on life satisfaction in adolescents with acne vulgaris. This study uses a correlational quantitative method with Satisfcation with Life Scale (SWLS), Multidimensional Body Self Relations Questionnaire – Appearrance Scales (MBSRQ-AS), and Iowa-Netherlands Comparison Orientation Scale as research instruments. The subjects of this study are adolescents with acne vulgaris as many as 352 people. Sampling was carried out by purposive sampling. This study uses multiple linear regression analysis. The results of the analysis revealed that body image affects life satisfaction and social comparison also affects life satisfaction. The two independent variables were also proven to jointly affect life satisfaction with a percentage of 39.2%.